Finite Element Modelling and Updating for Bolted Lap Joints / Rohaizat Omar...[et al.] - Omar, Rohaizat; Abdul Rani, Muhamad Norhisham; Wan Iskandar Mirza, Wan Imaan Izhan; Yunus, Mohd Azmi; Othman, Mohd Hakimi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Bolted joints have been widely used in the automotive and aerospace industries to join structural components due to its easy assembly method and low cost. However, the effect of the presence of bolted joints in industrial structures, regarding the dynamic response, has not been extensively studied, especially the efficient and economical modelling of the bolted joints itself. Therefore, this paper is put forward efficient and economical modelling for the bolted joints and interfaces affected regions of an assembled structure namely bolted lap joints. The finite element (FE) model of the bolted lap joints comprising the structural components, elements of the bolts, interfaces elements and the affected region of the interfaces were developed. Experimental modal analysis (EMA) was performed to extract the natural frequencies and mode shape of the physical lap joints’ components and the assembled structure. The FE modal analysis was conducted for the initial FE models of the structural components and the assembled structure, and there were errors obtained when the modal analysis results and the EMA results were compared. FE model updating procedure was used to minimise the errors in the initial FE models of structural components and assembled structure. Results show that the bolts’ material properties, stiffness values at the joint interfaces and the material properties of the interfaces affected regions have played a major role in ensuring the accuracy of the prediction of the dynamic behaviour of the bolted lap joint.